Image of underground theodolite (The Peerian Journal, 2024)
Marksheyderic imaging is a complex of geometric measurements and calculations, the preparation of mining plans, and the analytical work of geometric and mining tasks. Imaging will be carried out by the marksheyder service to fill out topographic plans, prepare special marksheyder plans on a large scale, and solve engineering issues.